دور اللغز في تعليمية النحو العربي وتيسيرة - شيادي، نصيرة (جامعة البليدة 2 علي لونيسي - كلية الآداب واللغات, 2021)
يعد النحو عمود اللغة فلا يكن أن نتصور لغة دون قواعد يسير عليها المتكلم. فلقد صرف النحويون في القرون الأولى جهودهم ومالهم ووقتهم في سبيل تقنين اللغة وصونها بسياج قواعد النحو العربي ولكن الملاحظ على الإنسان العربي حاليا معلما كان أو متعلما عزوفه عن هذا العلم؛ فالمعلم يشكو صعوبة تدريسه والمتعلم يشكو صعوبة فهمه؛ ولهذا ولما كان النحو مقوم الألسن، وروح اللغة، وعمود سنامها بات الاهتمام به أكثر من ضرورة وبالتالي فالهدف من هذا البحث هو طرح اقتراح من شأنه أن يحد من صعوبة تعلم وتعليم النحو العربي؛ اقتراح مفاذه توظيف اللغز في تعليم قواعد النحو العربي بغية تيسيره والتمكن منه وكذا تسهيل تعليمه وتعلمه Syntaxe is the backbone of language, it is impossible to picture a language without a set of rules on which the speaker bases their notions. Grammarians have always strived to rationalize and perfect language within a grammatical and syntaxial frame. However, it is noted that Arabs, whether learners or students, are reluctant to this science. Professors often complain about the difficulty of teaching it, whereas students have a hard time grasping its concepts. Therefore, and because syntaxe straightens the tongues and shapes the language spirits, it is important now, more than ever, to pay it its due attention. It is why this paper aims at raising a suggestion which would limit the difficulty of learning and teaching Arabic Syntaxe. This suggestion is to employ puzzles in teaching Arabic Grammatical syntaxe, in order to facilitate its grasp, and thus ease the learning-teaching process
Keywords: اللغة العربية -- الألفاظ والمفاهيم -- النحو البلاغي